Mangiferin Ameliorates Hyperuricemic Nephropathy Which Is Associated With Downregulation of AQP2 and Increased Urinary Uric Acid Excretion - Li, Xuechen; Yan, Zhenxin; Carlström, Mattias; Tian, Jinying; Zhang, Xiaolin; Zhang, Wenxuan; Wu, Song; Ye, Fei (Frontiers in Pharmacology, 2020)
Hyperuricemia is characterized by abnormally high level of circulating uric acid in the blood and is associated with increased risk of kidney injury. The pathophysiological mechanisms leading to hyperuricemic nephropathy (HN) involve oxidative stress, endothelial dysfunction, inflammation and fibrosis. Mangiferin is a bioactive C-glucoside xanthone, which has been exerting anti-inflammatory, anti-fibrotic and antioxidative effects in many diseases. This study aimed to evaluate the effect of mangiferin treatment in HN. In a mouse model of HN, we observed lower circulating urate levels and ameliorated renal dysfunction with mangiferin treatment, which was associated with reduced renal inflammation and fibrosis. We next investigated the mechanism of urate lowering effect of mangiferin. Metabolic cage experiment showed that mangiferin-administrated mice excreted significantly more urinary uric acid due to elevated urine output, but no marked change in urine uric acid concentration. Expressions of water channels and urate transporters were further assessed by western blot. Renal AQP2 expression was decreased, yet urate transporters URAT1, GLUT9 and OAT1 expressions were not affected by mangiferin in HN mice. Moreover, mangiferin treatment also normalized xanthine oxidase and SOD activity in HN mice, which would decrease uric acid synthesis and improve oxidative stress, respectively. Therefore, our results reveal a novel mechanism whereby mangiferin can reduce serum uric acid levels by promoting AQP2-related urinary uric acid excretion. This study suggested that mangiferin could be a multi-target therapeutic candidate to prevent HN via mechanisms that involve increased excretion and decreased production of uric acid and modulation of inflammatory, fibrotic and oxidative pathways.